Economic Distress and Electoral Consequences: Evidence from Appalachia - Firoozi, Daniel (The Review of Economics and Statistics, 2024)
Abstract Information about inequality can change political attitudes in lab and survey experiments. I use data from the Appalachian Regional Commission and a regression discontinuity design to test whether salient information about local poverty can impact voter behavior in a field setting. I find that when the poorest decile of counties is labeled “economically distressed,” the Democratic share of the Presidential and House popular vote rises in subsequent elections. I present suggestive evidence linking this result to local news coverage, rather than spending or other outcomes.